Impact of Single and Combined Faults Composed of Rotor Eccentricity and Stator Interturn Short Circuit on Electromagnetic Torque Ripples in Synchronous Generator. (25th March 2020) - He, Yu-Ling; Zhang, Zhi-Jie; Wang, Xiao-Long; Gao, Peng; Gerada, David; Gerada, Chris; Vakil, Gaurang
Abstract : In order to comprehensively study and identify the electromagnetic torque (EMT) difference among the single static air-gap eccentricity (SAGE) fault, the single stator interturn short circuit fault (SISC), and the combined fault composed of these two, this article investigates the EMT ripple properties due to the mentioned three faults. Different from other studies, this paper considers not only the effect of the single fault types but also the impact of the single fault combinations on the EMT ripple characteristics. Detailed EMT expressions for each fault are firstly derived on the basis of the magnetic flux density (MFD) analysis. Then, finite element calculation and experimental study on a CS-5 prototype generator with two poles at 3000 rpm, which is specifically designed and manufactured ourselves, are carried out to validate the analysis result. It is found that the three faults will induce different ripple components in EMT. The combined faults have the most intensive impact sensitivity on the EMT ripples, while the single SAGE fault ranks the last in the impact effect.